Crystal structure of dimethyl 5-(10-(methoxycarbonyl)anthracen-9-yl) isophthalate,C26H20O6 - Huang Xiang; Shi Da-Bin (Zeitschrift für Kristallographie - New Crystal Structures, 2018)
C26H20O6, monoclinic, P21/n (no. 14), a = 14.458(2) Å, b = 9.4176(18) Å, c = 16.914(3) Å, β = 113.429(5)°, V = 2113.1(6) Å3, Z = 4, Rgt(F) = 0.0676, wRref(F2) = 0.1935, T = 173(2) K.